Religious Leaders and Social Sustainability in Rural Communities in Indonesia ... - Najmu Tsaqib Akhda; ,F. Trisakti Haryadi; Siti Andarwati (Zenodo, 2023)
: In rural community development, social sustainability becomes an important factor besides economic and environmental sustainability. This study aims to examine how the role of religious leaders in rural areas in maintaining social sustainability. This study was conducted in rural areas in Central Java, Indonesia with a participatory observation approach. the results of this study indicate that the religious leaders become an agent in maintaining social sustainability. The communication skills of religious leaders and leadership types play a role in maintaining social systems and are able to create public space in rural community development activities. ... : {"references": ["Mahendra, Opik. 2016. \"Kepuasan Masyarakat terhadap Pengelolaan Dana Desa di Wilayah ProvinsiJawa Tengah\". UGM Graduate School, Yogyakarta: Gadjah Mada University", "Dhofier, Zamakhsyari. 1994. \"Tradisi Pesantren, Studi tentang Pandangan Hidup Kyai\". Jakarta: LP3ES.", "Neuman, W.L. 2007. \"Basics of Social Research: Qualitative and Quantitative Approaches\". Boston: Pearson Education.", "] Hare, A. Paul, (1985). \"Social Interaction As Drama: Aplications from Conflict Resolution\". London:.Sage Publication.", "Geertz, Clifford. 1983. \"Abangan Santri Priyayi dalam Masyarakat Jawa\". Jakarta: Terjemahan Pustaka Jaya", "Horikoshi, Hiroko. 1976. \"A Traditional Leader in a Time of Change: The Kyai and Ulama in West Java\". University of Illionis.", "Morreale, Sherwyn P., Brian H. Spitzberg, J. kevin Barge. 2007. \"Communication. Motivation, Knowledge, and Skills\". Canada: Thomson Wadsworth", "Weber, Max. 1968. \"The Sociology of Religion\". Boston: Beacon Press.", "Miner, John B. 2005. ...